Os pioneiros do Programa - do Rio, Gisela Pires (Espaço Aberto, 2022)
Profa. Maria do Carmo Correa Galvão (1925/...) Profa Bertha Koiffmann Becker (1930/2013) Prof. Jorge Xavier-da-Silva (1935/2021) Profa Maria Therezinha de Segadas Soares (1925/1993) Profa Lysia Maria Cavalcanti Bernardes (1924/1991) Profa Maria Regina Mousinho de Meis (1937/1985) Prof. Speridião Faissol (1923/1997)